THE ROLE OF JOB SATISFACTION AND PSYCHOLOGICAL WELL-BEING IN IMPROVING EMPLOYEE PERFORMANCE (STUDY IN PT. IHI POWER SERVICE INDONESIA) - Salsabila Damaihati; Fauji Sanusi; Roni Kambara (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to examine the effect of burnout on employee performance, with job satisfaction and psychological well-being as mediating variables. The research employs a quantitative approach, collecting data through questionnaires distributed to employees of PT. IHI Power Service Indonesia. The sampling technique used in this study is non-probability sampling, specifically the purposive sampling method, with a sample size of 107 respondents. Data analysis was conducted using Partial Least Squares (PLS) through the SmartPLS 4. The results indicate that burnout has a significant negative effect on employee performance and job satisfaction but has a non-significant negative effect on psychological well-being. Psychological well-being has a significant positive effect on job satisfaction, and job satisfaction has a significant positive effect on employee performance. Furthermore, job satisfaction is proven to mediate the relationship between burnout and employee performance in a significantly negative manner, whereas psychological well-being does not mediate the relationship between burnout and job satisfaction. These findings underscore the importance of managing burnout and enhancing job satisfaction to support employee performance.